Regulatory issues - informed consent for a device investigation. - Munzner, R.
For any patient about to undergo surgery, consent must be given; otherwise, the surgeon would be committing an assault. When a subject is to participate in a medical device investigation which is basically an experiment, a great deal more information is needed to assure that consent is really informed consent. Under the present rules for investigational devices in the United States, the primary source of objectivity is the review of consent materials by an institutional review board (IRB) composed of individuals having different interests, pursuits, and backgrounds. There must be at least five persons on the IRB, one of whom is not affiliated with the institution, and none may have a conflict of interest. Membership must include some persons who are knowledgeable in the particular area of research. To guide the review boards, or human research committees, in assuring that there is sufficient information for informed consent, the FDA rules require that specific elements be included in the information being provided to subjects who volunteer to participate in medical device or drug investigations. Although most of these elements are fairly explicit, that the risks and benefits description leaves room for interpretation by the IRB. IRBs as originally conceived were intended to be local and to interpret the degree of risk as the local community would perceive it.
Keywords: United States; Drug investigations; Human research committees; Informed consent; Institutional review board; Medical device investigation; Patient surgery; Regulatory issues; Risk assessment; Surgeon